ENERGY PREDICTION BASED ON MODELLING AND SIMULATION ANALYSIS OF AN ACTUAL GRID-CONNECTED PHOTOVOLTAIC POWER PLANT IN TURKEY - Çi̇çek, Osman; Millad, Mohamed Alageli M.; Erken, Faruk (INESEG Yayincilik, 2019)
Turkey has invested in generating solar power industry to meet the energy demand as well as saving the national energy resources. The government has also substituted some of the energy consumption with clean energy sources, especially on-grid PV power plants. In recent years, a number of incentives are provided to persuade investors to invest in solar energy sector in Turkey. In this context, KRMN-SNAPS 1.6 MW PV power plant is installed in Konya Province in the Central Anatolia region of Turkey. The most important information that have to be known in advance are the cost and duration of the investment. Therefore, pre-investment production analysis of the PV power plant is very essential. The performance of the power plant depends on some parameters for instance temperature, irradiance and sunshine duration. In this study, solar PV arrays are modelled and the power plant is simulated based on the above mentioned meteorological parameters. The simulation results of the PV power plant were compared with the actual production data. In the simulation, long-term average data on production of the location were used and it is observed that the simulation results and the one year's actual production data are compatible with each other.
Keywords: Renewable energy; PV systems; on-grid PV power plants; energy prediction; energy policy; Elektrik Mühendisliği; Electrical Engineering; 13. Climate action; 7. Clean energy